The effect of 1.5 T cardiac magnetic resonance on human circulating leucocytes. (18th November 2017) - Critchley, William R; Reid, Anna; Morris, Julie; Naish, Josephine H; Stone, John P; Ball, Alexandra L; Major, Triin; Clark, David; Waldron, Nick; Fortune, Christien; Lagan, Jakub; Lewis, Gavin A; et al.
Abstract: Aims: Investigators have proposed that cardiovascular magnetic resonance (CMR) should have restrictions similar to those of ionizing imaging techniques. We aimed to investigate the acute effect of 1.5 T CMR on leucocyte DNA integrity, cell counts, and function in vitro, and in a large cohort of patients in vivo . Methods and results: In vitro study: peripheral blood mononuclear cells (PBMCs) were isolated from healthy volunteers, and histone H2AX phosphorylation (γ-H2AX) expression, leucocyte counts, and functional parameters were quantified using flow cytometry under the following conditions: (i) immediately following PBMC isolation, (ii) after standing on the benchside as a temperature and time control, (iii) after a standard CMR scan. In vivo study: blood samples were taken from 64 consecutive consenting patients immediately before and after a standard clinical scan. Samples were analysed for γ-H2AX expression and leucocyte counts. CMR was not associated with a significant change in γ-H2AX expression in vitro or in vivo, although there were significant inter-patient variations. In vitro cell integrity and function did not change with CMR. There was a significant reduction in circulating T cells in vivo following CMR. Conclusion: 1.5 T CMR was not associated with DNA damage in vitro or in vivo . Histone H2AX phosphorylation expression varied markedly between individuals; therefore, small studies using γ-H2AX as a marker of DNA damage should be interpreted with caution. Cardiovascular magnetic resonance was not associated with loss of leucocyte viability or function in vitro. Cardiovascular magnetic resonance was associated with a statistically significant reduction in viable leucocytes in vivo .